Cortical excitability correlates with the event-related desynchronization during brain-computer interface control - Daly, Ian; Blanchard, Caroline C.V.; Holmes, Nicholas P. (IOP, 2018)
Objective: Brain-computer interfaces (BCIs) based on motor control have been suggested as tools for stroke rehabilitation. Some initial successes have been achieved with this approach, however the mechanism by which they work is not yet fully understand. One possible part of this mechanism is a, previously suggested, relationship between the strength of the event-related desynchronization (ERD), a neural correlate of motor imagination and execution, and corticospinal excitability. Additionally, a key component of BCIs used in neurorehabilitation is the provision of visual feedback to positively reinforce attempts at motor control. However, the ability of visual feedback of the ERD to modulate the activity in the motor system has not been fully explored. Approach: We investigate these relationships via transcranial magnetic stimulation delivered at different moments in the ongoing ERD related to hand contraction and relaxation during BCI control of a visual feedback bar. Main results: We identify a significant relationship between ERD strength and corticospinal excitability, and find that visual feedback does not affect corticospinal excitability. Significance: Our results imply that efforts to promote function recovery in stroke by targeting increases in corticospinal excitability may be aided by accounting for the time course of the ERD